Philippine medical thesaurus on psychiatry and psychology behavior and behavior mechanisms in Bicol - Risbud, Vidya S.; Tarlit, Rodolfo Y. (Quezon City Institute of Library and Information Science, University of the Philippines Diliman, 2005)
This study sought to translate terms from the Medical Subject Headings (MeSH) Facet F01 - Behavior and Behavior Mechanisms and to create Philippine Medical Thesaurus on Psychiatry and Psychology: Behavior and Behavior Mechanism in Bicol. The top-down approach or method, a basis of the framework of the domain analysis, was utilized to create thesaurus in Bicol. It uses existing implementations, the Medical Subject Headings (MeSH) in particular and ranked translation tools and supplements.
The population for this study is comprised of first language speakers of Bicol, in particular the Bicol of Legazpi City and who belong to the medical profession and may or may not be residents of the area. Out of the three hundred sixty-one (361) Behavior and Behavior Mechanisms terms under Psychiatry and Psychology downloaded, only two hundred thirty (230) terms were successfully translated to Bicol. The remaining one hundred thirty-one (131) terms not translated to Bicol, are indeed difficult to translate even with the availability of the ranked sources.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Subject headings, Bicolano -- Medicine; Subject headings, Bicolano -- Psychiatry; Subject headings, Bicolano -- Psychology; Bicolano language -- Medical Bicolano